Sistem Pendukung Harga Saham dengan Metode Linear Regression dan Simple Keputusan untuk Prediksi - Nefriardo Armaz, Ilham; Fryonanda, Harfebi (Institut Teknologi dan Bisnis Kalbis, 2020)
This research is conducted to solve existing problems in the stock market such as fluctuatingprices and decisions to be taken on the stock market. A common problem encountered is the difficultyof knowing stock price trends over a given period and using the analysis used in the stock market.Technical analysis allows to know stock market price based on trend by using Simple Moving Averagewhich have accuracy level 96,39 and Linear Regression which have accuracy level 94,91. The purposeof this research to produce decision support system that can be used as a prediction with the methodof Simple Moving Average and Linear Regression that can be compared the level of accuracy. Thisapplication is a solution to determine the stock price prediction in a certain period.